MANAJEMEN PENGELOLAAN WAKAF TANAH DI KECAMATAN PAGAR JATI KABUPATEN BENGKULU TENGAH - Intan Widuri; Desi Isnaini; Badaruddin Nurhab (JURNAL ILMIAH EDUNOMIKA, 2026)
This research is motivated by the problem of not optimal management of productive waqf assets in Pagar Jati District, Central Bengkulu Regency, which is mainly caused by the limited managerial capacity of nazhir at the local level. To dissect this problem, this study uses a descriptive qualitative methodology with a type of field research. Primary and secondary data were collected through in-depth interview techniques, direct observation, and documentation studies involving key information such as waqf nazhir, village governments, community leaders, and beneficiaries, then analyzed in a qualitative interactive manner. The discussion in this study focuses on an in-depth analysis related to the application of the operational management function which includes planning, organizing, implementing, and supervising funds as well as identifying inhibiting factors in the managerial process. The conclusion of the study shows that the management of land waqf has provided social benefits for the community, but its implementation is still faced with a number of obstacles, including weak archive management, disconnection of nazhir regeneration, low competence of human resources, limited funding, and the existence of cultural factors. Keywords : Wakqf Management, Nazhir, Land Waqf, Inhibiting Factors.